THE CORRELATION BETWEEN WAYS OF LEARNING AND ENVIRONMENT TOWARD STUDENT’S ENGLISH PRONUNCIATION AMONG THE SECOND GRADE OF SMPN 1 SEMEN - Rahayu, Eny Kusumaning (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This research is aimed to know whether there is significant correlation between ways of learning and environment toward student’s English Pronunciation simultaneously and partially among the second grade students of SMPN 1 Semen. The approach used is descriptive quantitative. The sample is 175 students. The instrument used ware questionnaire and test. The data analysis in this research was used descriptive and inferential statistic. The result showed there is no significant correlation between ways of learning and environment toward student’s English Pronunciation simultaneously and partially among the second grade students of SMPN 1 Semen. The value of correlation between X 1 , X 2 toward Y simultaneously was 0,08, and the level significant is 0,922 or more than 0.05. Then the value of X 1 and Y controlled by X 2 is -0.020, and the level significant is 0.797 or more than 0.05, then for correlation between X 2 and Y controlled by X 1 is 0.023, and the significant level is 0.766 or more than 0.05 too. It means that this research has no significant correlation among the three variables